Akurasi Pukulan Smash pada Atlet Bulutangkis Pb Talenta Kebumen Menggunakan Metode Drill Usia 9-12 Tahun : Penelitian - Mokhamad Parmadi; Aditya Singgih Kurniawan (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The problem that arises is that there are still players who do the wrong smash technique, for example, the hit on the shuttlecock is not right. The purpose of this study was to determine the accuracy of the smash stroke in badminton athletes of PB Talenta Kebumen aged 9-12 years. This study uses a quantitative descriptive research type with a survey method, the instrument used in this study is a smash test skill test. Each athlete is given 10 opportunities to do a smash stroke alternately. Athletes are given the opportunity to try a smash stroke, namely 2 straight and cross smash strokes. Based on research that has been conducted on badminton athletes of PB Talenta Kebumen, the level of smash accuracy in the majority of samples is in the very good category 33% or 4 athletes, good category 33% or 4 athletes, moderate category 17% or 2 athletes, low category 17% or 2 athletes and very low category 0% or none. Factors that affect smash accuracy include how to hold the racket, foot position, footwork, arm swing.